A contraction theorem in fuzzy metric spaces. Issue 3 (25th October 2005) - Razani, Abdolrahman
Abstract : A fixed point theorem is proved. Moreover, fuzzy Edelstein's contraction theorem is described. Finally, the existence of at least one periodic point is shown.